Nutritional, bioactive, and antimicrobial analysis of powders and ethanolic extracts of three important halophyte plants (Anabasis articulata, Lycium shawii, and Zilla spinosa), and their application in bakery product - Hussain, Ashiq; Mouhaddach, Aziz; Khalid, Ibtissame; Kausar, Tusneem; Bouhrim, Mohamed; Shahat, Abdelaaty A.; Noman, Omar M.; Eto, Bruno; Yaqub, Shazia; Arshad, Rizwan; Farooq, Humna; Firdous, Nida; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionNew alternate food and pharma sources, halophyte plants have long been displaying exceptional nutritional and functional qualities.MethodsPresent investigations were carried out to explore three important halophyte herbs; Anabasis articulata, Lycium shawii, and Zilla spinosa,harvested from deserts, for phytochemical composition and potential food application.Results and discussionPlant leaves, converted into powders showed significant amounts of ash, fiber, and important minerals as contents (%) of ash and fiber in Anabasis articulata, Lycium shawii, and Zilla spinosa were 6.39 and 6.79, 8.19 and 9.14, and 4.35 and 8.87, respectively, while Mg, Zn, Cu and Mn were significantly higher in Anabasis articulata, with values 52.40, 50.59, 16.33 and 48.25 mg/kg, respectively, whereas Zilla spinosa presented Fe as 120.95 mg/kg, highest from all. Total phenolic contents (45.92 mg gallic acid equivalent/g), total flavonoid contents (11.31 mg quercetin equivalent/g) and total antioxidant activity (22.85 mg Trolox/g) were found highest in ethanolic extract of Lycium shawii, while in remaining two plants these values were also prominent. Extracts of these three halophytes leaves exhibited prominent antimicrobial activities, as calculated zone of inhibitions (mm) were comparable to reference drugs. Incorporation of powders of all three halophytes resulted in significant increment in ash fiber and minerals (Mg, Zn, Fe, Cu and Mn) content of biscuits but with slight decrement in moisture, fat and protein. Formulated biscuits were also found boosted in total phenolic and flavonoid contents with elevated antioxidant activity as a result of incorporation of halophytes powders. Assessment of biscuits revealed that 5% levels of all halophyte’s powders produced acceptable product in terms of color, taste, texture and overall acceptability. Thus, halophyte plant powders and extracts could be used as new and sustainable source for food and pharma products.